El procedimiento administrativo sancionador como medio de control en la administración pública - Romo Castillo, Jhully Pacyn (2022)
The Superintendence of Companies, Insurance and Securities, being a body with autonomy, is responsible for the proper functioning and control of economic and social activities to ensure that their actions are covered by the regulations, since there are many irregularities in the administrative sanctioning procedure, for which we want to analyze the deficiencies in the regulation of the Administrative Organic Code COA, since omitting the deadlines for the statute of limitations to apply sanctions would result in many administrative acts contrary to due process. The Administrative Organic Code establishes new rules for the sanctioning power of each public entity, in the proposed case we concentrate on the actions carried out in the Superintendence of Companies, Securities and Insurance, this power is similar to ius puniendi in criminal matters, that is, it allows the entity to establish sanctions or punishments of economic nature (fines) for those who have breached in any way the rules established in that area...........